English Nursery Rhymes in the U. S.: The Importance of Cultural Aspects in Education - Rausch-Molnár, Luca (AMERICANA E-journal of American Studies in Hungary, 2024)
Nursery rhymes have long been perceived as fundamental in young children’s education, not only in a first-language environment, but also in foreign language teaching. While most research focuses on the benefits of rhymes, rhythm, as well as the playful features of nursery rhymes, the aim of this article is to emphasize the importance of their function as transmitters of cultural values. The role of oral tradition was, originally, rather to preserve, process and reflect on cultural and historical events and crises than to educate children. Still, most American nursery rhymes have origins rooted in British tradition and culture, which means that culturally specific content in British nursery rhymes should be interpreted in an American cultural context. It is by analyzing and retracing the origins of four British nursery rhymes widely known in the Unites States that the paper intends to show how these rhymes remain social models and serve cultural educational purposes today.